1998
DOI: 10.1046/j.1471-4159.1998.70030993.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Human Glutamate Transporter Activity by Phorbol Ester

Abstract: Termination of synaptic glutamate transmission depends on rapid removal of glutamate by neuronal and glial high-affinity transporters. Molecular biological and pharmacological studies have demonstrated that at least five subtypes of Na~-dependent mammalian glutamate transporters exist. Our study demonstrates that Y-79 human retinoblastoma cells express a single Na~-dependent glutamate uptake system with a Km of 1.7 ±0.42 1iM that is inhibited by dihydrokainate and DLthreo-~3-hydroxyaspartate (IC50 = 0.29 ±0.17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…In the present study, the primary astrocyte cultures were prepared from cerebral cortex of rats where GLT-1 represents the predominant glial transporter (O'Shea et al, 2006;Marco and Michael, 2004). It has been reported that activation of PKC caused internalization of GLT-1 and decreased in cellsurface expression of GLT-1 (Kalandadze et al, 2002); PKC activation also inhibited the traffic process of GLT-1 whereby PKC phosphorylation reduced the function of GLT-1 (Ganel and Crosson, 1998). The present study showed that treatment with diazoxide and iptakalim inhibited PKC phosphorylation, thus it is reasonable to presume that inhibiting PKC phosphorylation by KCOs facilitates glutamate uptake.…”
Section: Kcos Suppressed Pkc Activity In Mpp + -Treated Astrocyte Culsupporting
confidence: 61%
“…In the present study, the primary astrocyte cultures were prepared from cerebral cortex of rats where GLT-1 represents the predominant glial transporter (O'Shea et al, 2006;Marco and Michael, 2004). It has been reported that activation of PKC caused internalization of GLT-1 and decreased in cellsurface expression of GLT-1 (Kalandadze et al, 2002); PKC activation also inhibited the traffic process of GLT-1 whereby PKC phosphorylation reduced the function of GLT-1 (Ganel and Crosson, 1998). The present study showed that treatment with diazoxide and iptakalim inhibited PKC phosphorylation, thus it is reasonable to presume that inhibiting PKC phosphorylation by KCOs facilitates glutamate uptake.…”
Section: Kcos Suppressed Pkc Activity In Mpp + -Treated Astrocyte Culsupporting
confidence: 61%
“…29 -31). The effects of PKC activators on the activity of GLT-1 are varied and may depend on cellular environment (12)(13)(14)(15). Therefore, we initially examined the effect of shortterm activation of PKC on the cell surface expression of GLT-1 using primary co-cultures of neurons and astrocytes derived from embryonic rat cortex.…”
Section: Effects Of a Pkc Activator On Cell Surface Expression Andmentioning
confidence: 99%
“…For example, activation of PKC causes an increase in activity when GLT-1 is expressed in HeLa cells using vaccinia virus (12) but has no effect on the activity of GLT-1 stably transfected into HeLa cells or two other peripheral cell lines (13). In a cell line that endogenously expresses the human variant of GLT-1 (Y-79 human retinoblastoma), activation of PKC causes a decrease in activity by increasing the K m value for transport (14). In a preliminary study, activation of PKC caused a decrease in GLT-1 activity in stably transfected Madin-Darby canine kidney cells (15).…”
mentioning
confidence: 99%
“…Although Casado and colleagues originally suggested that activation of PKC increases activity in GLT-1-transfected HeLA cells (Casado et al, 1993), we were unable to replicate this result (Tan et al, 1999). In primary cultures derived from rat brain and Y-79 human retinoblastoma cells that endogenously express GLT-1, activation of PKC rapidly (within min) decreases GLT-1-mediated transport activity and reduces the amount of GLT-1 that is observed at the plasma membrane (Ganel andCrosson, 1998 Kalandadze et al, 2002;Zhou and Sutherland, 2004;Guillet et al, 2005). Similar effects have been observed in C6 glioma cells or Madin-Darby canine kidney cells transfected with GLT-1 (Carrick and Dunlop, 1999;Kalandadze et al, 2002;Zhou and Sutherland, 2004).…”
Section: Introductionmentioning
confidence: 99%